Determinan Premium Resiko Saham Industri Manufaktur Indeks Lq-45 Yang Terdaftar di BEI Periode 2017 – 2023 - Ramdan, Muhamad; Manurung, Adler Haymans; Silalahi, Edward Efendi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Determinants of the Risk Premium of Manufacturing Industry Stocks of the LQ-45 Index Listed on the IDX for the 2017-2023 Period. This study aims to determine the Determinants of the Risk Premium of Manufacturing Industry Stocks of the LQ-45 Index listed on the IDX for the 2017-2023 Period. The data used in this study are secondary data. The data are quantitative data obtained from the Indonesia Stock Exchange (IDX) with stocks included in the LQ-45 Index in the form of annual financial reports for the period 2017 - 2023. The research sample was 32 companies obtained using the purposive sampling technique. The data analysis technique used is multiple linear regression analysis and hypothesis testing using a partial t-test, a simultaneous F-test and a determination coefficient test. The data analysis technique was carried out using the Eviews 13 for Windows program. The results of the study indicate that premium, net profit margin and debt to equity ratio have a significant effect on equity risk premium, Variable Premium partially has a positive effect on Equity Risk Premium. Meanwhile, the Net Profit Margin and Debt to Equity Ratio variables have a negative influence on the Equity Risk Premium.